REWANG: KEARIFAN LOKAL DALAM MEMBANGUN SOLIDARITAS DAN INTEGRASI SOSIAL MASYARAKAT DI DESA BUKIT BATU KABUPATEN BENGKALIS - Hasbullah Hasbullah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
W'isdom localing to constitute proprietary wisdom form by society that happens in tempoh so long, time. In local wisdom to be contained positive point that become guidance for deep society gets behaviour: Yaw as shaped as tradition which contain society Local wisdom Hill Petrifies in solves various work up to happen it wedding ceremony. Yaw not only contain royong's carry elemen" but also available social solidarity element (social solidarity), and social integration. Participants yaw feels equal to sacrify energy, time, and also money